The Egyptian Journal of Critical Care Medicine - Fahmy, Tamer; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Egyptian Journal of Critical Care Medicine is the official Journal of the Egyptian College of Critical Care Physicians, the most authoritative organization of Egyptian physicians involved in the multi-professional field of critical care medicine. The journal is intended to provide a peer-reviewed source for multidisciplinary coverage of general acute and intensive care medicine and its various subcategories including cardiac, pulmonary, neuro, renal, and post-operative care. The journal is proud to have an international multi-professional editorial board in the broad field of critical care that will assist in publishing promising research and breakthrough reports that lead to better patient care in life-threatening conditions and bring the reader quick access to the latest diagnostic and therapeutic approaches in monitoring and management of critically ill patients. .
Keywords: Surgery; Critical care medicine; Surgery; Intensive Care Medicine